Low Serum Testosterone Concentrations Are Associated With Poor Cognitive Performance in Older Men but Not Women - Dong, Xue; Jiang, Hong; Li, Suyun; Zhang, Dongfeng (Frontiers in Aging Neuroscience, 2021)
OBJECTIVE: Current evidence on the association between serum testosterone and cognitive performance has been inconsistent, especially in older adults. To investigate the associations between serum testosterone and cognitive performance in a nationally representative sample of older men and women. METHODS: We used data from the National Health and Nutrition Examination Survey (NHANES) 2011–2014. 1,303 men and 1,349 women aged 60 years or older were included in the study. Serum total testosterone was preformed via isotope dilution liquid chromatography tandem mass spectrometry (ID-LC-MS/MS) method. Free testosterone was calculated by Vermeulen's formula. Cognitive performance was evaluated by the Consortium to Establish a Registry for Alzheimer’s Disease (CERAD) test, Animal Fluency test, and Digit Symbol Substitution Test (DSST). Binary logistic regression and restricted cubic spline models were applied to evaluate the association of testosterone and cognitive performance. RESULTS: In men, higher concentrations of total testosterone were associated with better performance on CERAD test (OR = 0.51; 95%CI = 0.27-0.95) and DSST (OR = 0.54; 95%CI = 0.30-0.99) in adjusted group. Similarly, higher concentrations of free testosterone were associated with better performance on CERAD test (OR = 0.32; 95%CI = 0.17-0.61) and DSST (OR = 0.41; 95%CI = 0.17-0.96) in men. These associations were not seen in women. CONCLUSION: Serum testosterone concentrations were inversely associated with cognitive performance in older men but not women in the United States.